The Mediating Role of Access to Digital Finance on the Relationship between Financial Literacy and Performance of Uganda SMEs in Mbarara City - Bakashaba, Rennie; Musiita, Benjamin; Nabachwa, Sarah (Journal of Economics and Behavioral Studies, 2024)
The study aimed to explore the potential mediating influence of access to digital finance in the relationship between financial literacy and the performance of SMEs in Uganda. To establish this link, the study used a cross-sectional methodology to collect data at a certain point in time. Barron and Kenney’s (1986) four phases required each direct influence of the study variables to follow a significant criterion. These requirements were satisfied because there was a significant direct correlation between SMEs’ performance and financial literacy (Beta= 0.655; p<.01). Access to digital finance and financial literacy demonstrated a considerable direct impact (Beta= 0.519; p<.01). Moreover, there was a noteworthy direct impact from SMEs’ performance to their access to digital finance (Beta=0.491; p<.01). When considering access to digital finance, the direct association between financial literacy and SMEs’ performance decreased from Beta=0.655 to Beta=0.548, remaining statistically significant. This indicates that access to digital finance might serve as a moderator in the connection between financial literacy and SME success. further demonstrated by the indirect effect of (0.106/0.655 x 100) percentage. 16.2%, meaning that the direct effect is explained by 83.8% in the model. It is advised that policymakers and stakeholders in Uganda’s SME sector should concentrate on developing clear guidelines on how SME owners can access digital finance. This will help in training them to improve the performance of SMEs. To improve SME outcomes, methods should be developed to make it simpler for people to use digital financial services and raise their financial literacy.